2008
DOI: 10.1007/s11595-007-5712-2
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial reaction between solid nickel and liquid zinc

Abstract: Interfacial reactions between solid nickel and liquid zinc at 450-650 ℃ for 30-600 s were studied. The morphology and growth behavior of intermetallic compound layers at the interface between solid nickel and liquid zinc were observed and analyzed by SEM and EDS. The results show thatγand δ phases are formed at 450 ℃ at the Ni/Zn interface, and at 550 and 650 ℃ ℃ onlyγphase is formed at the interface and someδ phase particles will be participated during solidification on the surface ofγphase layer. Theβ 1 phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…6. On the other hand, as mentioned in Section 1, the reactive diffusion between solid Ni and liquid Zn was experimentally observed by Kong et al 39) In their experiment, Ni/Zn diffusion couples were prepared by an immersion technique and then isothermally annealed at temperatures of T = 723923 K. An intermetallic layer consisting of the £ and ¤ phases formed at the original interface in the Ni/Zn diffusion couple at T = 723 K. At T = 823923 K, however, the ¤ phase was not detected in the intermetallic layer. Their values of the layer thickness l for T = 923 K are plotted against the annealing time t as open squares in Fig.…”
Section: Comparison With Other Resultsmentioning
confidence: 67%
See 4 more Smart Citations
“…6. On the other hand, as mentioned in Section 1, the reactive diffusion between solid Ni and liquid Zn was experimentally observed by Kong et al 39) In their experiment, Ni/Zn diffusion couples were prepared by an immersion technique and then isothermally annealed at temperatures of T = 723923 K. An intermetallic layer consisting of the £ and ¤ phases formed at the original interface in the Ni/Zn diffusion couple at T = 723 K. At T = 823923 K, however, the ¤ phase was not detected in the intermetallic layer. Their values of the layer thickness l for T = 923 K are plotted against the annealing time t as open squares in Fig.…”
Section: Comparison With Other Resultsmentioning
confidence: 67%
“…where K is the parabolic coefficient with a dimension of m 2 /s. The values of K reported by Kong et al 39) are shown as open squares in Fig. 7.…”
Section: Comparison With Other Resultsmentioning
confidence: 91%
See 3 more Smart Citations